Assessing the weaknesses and strengths of assessment and evaluation methods and teacher scoring methods in schools and providing solutions for improving existing status - Nabavizadeh, Zahra; Ghaltash, Abbas (IJRDO- Journal of Educational Research, 2018)
The present study examines Assessing the weaknesses and strengths of assessment and evaluation methods and teacher scoring methods in schools and providing solutions for improving existing status. In this regard, the factors used in evaluating and the methods of school teacher scoring and its weaknesses and strengths are examined. The method of doing this research is analytically descriptive in a library way. The content analysis of texts and documents related to evaluation methods and exponential reality were used to gather information. The complex measurement process will force teachers to make professional decisions to align their classroom realities with the impact of external factors. The findings and suggestions of this study provide planners and decision makers with guidelines for review, decision making and planning for successful assessment and teacher scoring practices.